The Role of Christians in The Correlation between The Notion of Lex Orandi, Lex Credendi, Lex Vivendi and The Commitment of Cape Town - Paulus Jinu Kim (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2022)
Lex orandi, lex credendi, lex vivendi is conventional concepts of the Christian life, but those are still relevant to solve problems of modern society. The interconnectedness of worship (lex orandi), theology (lex credendi), life (lex vivendi) is emphasized in the Christian sphere. Nevertheless, God's mission as the role of Christians was not highlighted in their relationship. The Commitment of Cape Town strongly stresses that Christians accomplishes God's mission with holistic ways in domains of gospel, world, church. In this study, the notion of lex orandi, lex credendi, lex vivendi will be explained about relationship and interaction. Then the Commitment of Cape Town will be analyzed in detail in connection with lex orandi, lex credendi, lex vivendi. The researcher uses the literature review method with answer to one question, that is ‘what is the true role of Christians in the world?’ The result of this study concluded that when Christians stand before God holistically in the notion of lex orandi, lex credendi, and lex vivendi, Christians can live by accomplishing God's mission in the church, with gospel, and into the world.